Effect of an Error in the Forward Difference based tabular values of the Rate of Enzymatic Reaction based Mathematical Functions - Uddin, Nizam; Mohammed, Saad (International Journal of Pharmacology and Toxicology, 2013)
In this research paper, we explained the effect of an error in the tabular values of substrate concentration, enzyme concentration and temperature with the rate of enzymatic reaction. All values are in interval. These values are obtained by mathematical functions of the rate of enzymatic reaction. Mathematical functions show that the concentration of substrate is the limiting factor, as the substrate concentration increases, the Enzyme reaction rate increases. Assuming a sufficient concentration of substrate is available, increasing Enzyme concentration will increase the rate of enzymatic reaction. Temperature, concentration of substrate and concentration of enzyme are increased the rate of enzymatic reaction at a limit which is called optimum limit. We take these values in tabular form with forward difference and added an error in the tabular values of substrate concentration, enzyme concentration and temperature with the rate of enzymatic reaction. Tabular values show the erroneous values. There are changes in tabular values. The effect of an error goes increasing with the succession. The coefficients of “?” are the binomial coefficients with alternating signs. In various difference columns of the difference table, the algebraic sum of the error is zero. The maximum error occurs in the same line as the erroneous tabular value. This is show the effect of tabular values of substrate concentration, enzyme concentration and temperature with the rate of enzymatic reaction.